Complication Following percutaneous coronary intervention via the femoral artery Experience in lraqi center for the Heart Disease and lbn Al-Bitar Hospital for cardiac surgery. - Majeed, Salah M.; Bahjet Al Saffar, Hilal; AL- Marayati, Amal N. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Vascular complications have been recognized as an important factor in morbidity after diagnostic and percutaneous coronary interventions. Objectives: This study sought to evaluate vascular complications after diagnostic coronary angiography and percutaneous coronary intervention (PCI) from the common femoral artery. Patients and methods: This prospective cohort study was carried out over a year period, from February 2008 till January 2009, at the Iraqi Center for the Heart Disease and Ibn Al-Bitar Hospital for Cardiac Surgery. A total number of 2400 patients underwent 3600 procedures, diagnostic coronary angiography (2196) and PCI(1404) via their common femoral arteries were included in this study. Result: A total 407(11.3%) patients developed different vascular complications (retroperitoneal hematoma, loss of distal pulse, arterial perforation each of them 0.03%, bruises 8.9%, pseudoaneurysm 0.69%, AV fistula 0.03%, hematoma ≥10cm 0.3% and <10cm 1.2%). We identified multiple factors associated with increased frequency of vascular complications like age, gender and past medical history. We have more frequent minor complications and more attendance to treat our complications surgically. Conclusions: This study has shown that the vascular complications continue to occur post PCI and diagnostic coronary angiography.